STRATEGI PEMASARAN AGROINDUSTRI BALADO KERIPIK KENTANG DAGING (KRITING) - Nurhana Jafaruddin; Cecep Pardani (Universitas Galuh, 2022)
This study aims to identify internal and external factors and formulate alternative marketing strategies for meat potato chips agro-industry. The research location was taken purposively, using the case study method. This study uses IFE and EFE analysis and SWOT analysis. The results obtained are internal factors consisting of product strengths and weaknesses where the strengths are guaranteed raw material continuity, motivation to develop business, online product marketing, halal products, non-MSG products, safe and attractive product packaging, semi-modern production equipment. The weakness of the product is limited capital, no offline store, lack of product flavor variant innovation, the product does not have a PIRT permit. External factors include opportunities and threats from the product. Opportunities for products that have the potential to be used as souvenir products, wider product market share, product diversification, products are good for health. Some of the threats to business actors are competitors offering products at relatively lower prices, fluctuating production material prices, and a decrease in turnover in the circumstances of the Covid-19 pandemic. Marketing strategy as an alternative strategy from external and internal factors is promoting at various events. such as bazaars or local events as well as opening collaborations with product resellers in various regions, making product differentiation and completing PIRT permits, collaborating with other souvenir products and being marketed online, as well as promoting product education.